New insights from recent studies in historical astronomy : following in the footsteps of F. Richard Stephenson : a meeting to honor F. Richard Stephenson on his 70th birthday /: following in the footsteps of F. Richard Stephenson : a meeting to honor F. Richard Stephenson on his 70th birthday. ([2014]) - Unknown
No abstract available